Ta Tawwur Al-lughat Al-'arabiyyah - Azman Ismail (Universitas Islam Negeri Ar-Raniry, 2001)
Change is an unstoppable phenomenon. As society experiences, some changes so does the language. In any language, vocabularies constitute the most rapid aspect that develops in accordance with time, while grammar is the slowest one. As far as Arabic is a concern, it is divided into both poetry and prose. The Arabic poetry that consisted of sixteen meters was seen to have been improper by the Arab who moved to Andalusia, Spain. In the meantime, the Arabic grammar contained in Sibawayhi’s work was eventually adopted by the Cairo Center of Language, which developed some new styles of tenses.